Leitura no âmbito do PNAIC : um estudo bibliográfico em teses e dissertações - Soares, Helenice de Aguiar (2021)
This investigation is linked to the Research Group ALFALE - Alphabetization and School Literacy, to the Postgraduate Program in Education - Human and Social Sciences Institute, of the Federal University of Mato Grosso, currently Federal University of Rondonópolis (UFR), in the research line: Languages, Culture and Knowledge Construction: historical and contemporary perspectives. The research has as general objective analyze the reading approaches in dissertations and theses in the National Pact for Literacy in the Right Age (PNAIC) and published in the Brazilian Digital Library of Dissertations and Theses (BDTD) in the period of 2013 and 2019. The specific objectives are: a) investigate, in the scientific productions mentioned, the reading approach; b) map data in levels of academy, regions of defense; post-graduate programs, fields of knowledge, theoretical-methodological references of the analyzed papers. The decision of studying reading in the scope of PNAIC emerges from the following question: What are the reading approaches in dissertations and theses in the PNAIC and published in BDTD? The constitution of the corpus of the research arises from the data collection in the BDTD platform of the Brazilian Institute of Information in Sciences and Technology (IBICT), available on the site www.bdtd.ibct.br. In the range of the research were found 71 (seventy-one) papers, being 63 (sixty-three) master theses and 08 (eight) doctorate dissertations. This study developed through a qualitative, descriptive, exploratory approach, with theoretical-bibliographic procedures in the modality State of Knowledge. It was sought, for this research, the theoretical framework of Ana Teberosky and Teresa Colomer (2003), Anna Camps and Teresa Colomer (2002), Isabel Solé (1998), Leffa (1996) and Mary Kato (1990) among others. For data analysis, the principles of Content Analysis were adopted, as recommends Bardin (2016). This enabled the systematization of the data and the definition of the following thematic categories: Reading in relation to the teaching practice and to teaching; Reading in relation to the studies of the education workbooks of PNAIC. The results evidenced the readings mediated by the teaching action developed in the educational sphere, implemented by educational practices to promote teaching based on activities with children literature, literature for pleasure, didactic sequence and text genres. As far as the reading conceptions, it was evident that it is privileged the reading in the interactive process in which the individual participates actively engaging previous knowledges and of the world, in a construction of meanings. It is perceived a bigger emphasis on papers on the appropriation of writing rather than on reading.